ANALISIS NEET (NOT IN EMPLOYMENT, EDUCATION OR TRAINING) PADA GEN Z USIA PRODUKTIF DI PROVINSI NUSA TENGGARA TIMUR - Hery Wahyu (Badan Pusat Statistik Provinsi NTT, 2026)
The phenomenon of Not in Employment, Education, or Training (NEET) among youth, particularly Generation Z (Gen Z), poses an important challenge to Indonesia’s human capital development. Although the national NEET rate declined from 24.28 percent in 2020 to 20.31 percent in 2024, the figure remains sufficiently high to indicate that many productive-age youth are still not fully engaged in education, training, or the labor market. A similar condition is observed in East Nusa Tenggara (NTT), which records a NEET rate of 14.1 percent and has the highest dependency ratio nationally, reaching 61.6 percent based on the 2035 population projection. These circumstances highlight the need to maximize the participation of the productive-age population to ensure that the demographic bonus is effectively utilized rather than becoming a demographic burden. This study analyses the NEET status of productive-age Gen Z in NTT and examines the determinants influencing NEET outcomes using binary logistic regression. The independent variables considered include gender, age group, marital status, disability status, area of residence, highest educational attainment, and household size. The results show that all variables have a significant effect on the likelihood of Gen Z being categorized as NEET. Keywords: Gen Z, NEET, binary logistic regression